Assessment of the processing profile of six “creole potato” genotypes (solanum tuberosum phureja group) (2011)
Six diploid potato (“creole potato”, Solanum tuberosum PhurejaGroup) genotypes were grown at the localities of Soacha, Duitama and Mosquera (Colombia) and were assessed for their suitability for industrial processing using Individual Quick Freezing (IQF) as pickled and dehydrated (flakes) potatoes. The following variables were assessed: Percentage of defective tubers, dry weight, specific gravity, “eye” depth, skin type, shape, appearance, color, aroma, flavor and texture. Cultivar Criolla Colombia and clone 98-71.26 showed the best behavior for precooking processing. The best characteristics for IQF and pickling corresponded to tubers with yellow colored peel, round shape, shallow “eyes”, 16 to 20.5% dry weight, 2.5 to 3.5 cm diameter and less than 0.1% reducing sugars. For dehydrated flakes the tubers with 21-25% dry weight, large size and reducing sugars below 0.1% exhibited the best processing behavior. In addition, it was observed that the cultivar’s environmental conditions affect tuber quality and processing type to be performed.